Kylie Jean Fashion queen - Peschke (North Mankato, MN Picture Window Books, a Capstone imprint, 2015)
Inspired by the beautiful dresses at the Academy Awards show, Kylie Jean decides to try her hand at fashion--and Lilly recruits her to model the dress she is making for a school fund raising auction
Arts ( design)
a gift from book africa
1 2 13 15
Keywords: Fashion design -- Juvenile fiction; Fashion shows -- Juvenile fiction; Models (Persons) -- Juvenile fiction